The Effect of Citrus amblycarpa Hassk Extract Against Rattus norvegicus Body Weight with High-Fat Diet - Roselina Panghiyangani; Juliyatin Putri Utami; Lena Rosida; Dewi Indah Noviana Pratiwi (Universitas Muhammadiyah Semarang, 2023)
Background: Obesity is a complex disease that is generally accompanied by insulin resistance and increased oxidative stress and the expression of inflammatory markers that contribute to the accumulation of body fat mass. Lemons contain high levels of flavonoids and essential oils so that they have the potential to control appetite and play a role in fat breakdown. Purpose: to determine the effect of Citrus amblycarpa Hass extract on weight loss of rats fed a high-fat diet.Objective: Rattus novergicus Wistar strain aged 2-3 months and randomly divided into 6 groupsMethods: The dried Citrus amblycarpa Hass peel was extracted by maceration method with 70% ethanol as solvent. Variations in the dose of Citrus amblycarpa Hass peel extract given were 200, 300 and 400 mg/kg BW. There were 6 groups of treated rats with 30 rats total sample. The weight of the mice from each treatment group was measured for 6 weeks and then the average body weight of each group was analyzed using Kruskall Wallis with the Mann-Whitney further test.Results: The data showed that administration of Citrus amblycarpa Hass peel extract had a significant effect on weight loss of Wistar rats fed a high-fat diet with p= 0.00 (p <0.05). The average body weight of the 300 mg/kg BW and 400 mg/kg BW extract treated rats was significantly different from the control group that was not given the C. amblycarpa Hass peel extract, but the average body weight in the 200 mg/kg BW dose group did not show a significant difference.Conclusion: There is an effect of C. amblycarpa Hass peel extract in reducing the body weight of Wistar rats fed a high-fat diet significantly at doses of 300 mg/kg BW and 400 mg/kg BW.